Pengaruh Sistem Aplikasi Pusat Keuangan, Budaya Organisasi, dan Komitmen Kerja terhadap Kepuasan Kerja Operator Tunjangan Kinerja pada Urusan Keuangan di Satuan Kerja Lingkungan Mabes Polri Tahun 2024 - Anggraeni, Shintia; Sinambela, Lijan P. (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to identify the impact of the Central Financial Application System, organizational culture, and work commitment on the job satisfaction levels of performance allowance operators within the financial units of the Indonesian National Police Headquarters (Mabes Polri) in 2024. A quantitative approach was employed, analyzing the entire population consisting of 130 respondents, including treasurers and performance allowance operators. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 25. The results demonstrate that, collectively, the three independent variables have a significant effect on job satisfaction (F-count = 101.473, significance = 0.000 < 0.05). Individually, the Central Financial Application System (b = 0.385; sig. = 0.000), organizational culture (b = 0.328; sig. = 0.000), and work commitment (b = 0.126; sig. = 0.015) each have a positive and statistically significant impact on the job satisfaction of performance allowance operators. The adjusted R² value of 0.707 indicates that approximately 70.7% of the variance in job satisfaction can be explained by these three variables. These findings highlight the strategic importance of continuously improving the effectiveness of financial application systems, strengthening positive organizational culture, and fostering higher levels of work commitment. Together, these factors are critical to supporting efficient financial management and enhancing employee satisfaction within the organizational structure of the Indonesian National Police.